The late endosomal HOPS complex anchors active G-protein signaling essential for pathogenesis in magnaporthe oryzae - Ramanujam, Ravikrishna. (2013)
In Magnaporthe oryzae, the causal ascomycete of the devastating rice blast disease, the conidial germ tube tip must sense and respond to a wide array of requisite cues from the host in order to switch from polarized to isotropic growth, ultimately forming the dome-shaped infection cell known as the appressorium. Although the role for G-protein mediated Cyclic AMP signaling in appressorium formation was first identified almost two decades ago, little is known about the spatio-temporal dynamics of the cascade and how the signal is transmitted through the intracellular network during cell growth and morphogenesis. In this study, we demonstrate that the late endosomal compartments, comprising of a PI3P-rich (Phosphatidylinositol 3-phosphate) highly dynamic tubulo-vesicular network, scaffold active MagA/GαS, Rgs1 (a GAP for MagA), Adenylate cyclase and Pth11 (a non-canonical GPCR) in the likely absence of AKAP-like anchors during early pathogenic development in M. oryzae. Loss of HOPS component Vps39 and consequently the late endosomal function caused a disruption of adenylate cyclase localization, cAMP signaling and appressorium formation. Remarkably, exogenous cAMP rescued the appressorium formation defects associated with VPS39 deletion in M. oryzae. We propose that sequestration of key G-protein signaling components on dynamic late endosomes and/or endolysosomes, provides an effective molecular means to compartmentalize and control the spatio-temporal activation and rapid downregulation (likely via vacuolar degradation) of cAMP signaling amidst changing cellular geometry during pathogenic development in M. oryzae.